New Aspects of the Antibiotics Use in Ophthalmology: the View of a Clinical Pharmacologist - G. Yu. Knorring (Oftalʹmologiâ)
For infectious and inflammatory eye lesions, the main methods of controlling pathogens include antibacterial agents of various classes and antiseptics. However, the use of these agents has a number of limitations: they are able to act primarily on the surface of the eye tissue, and in accordance with clinical recommendations, they should be used as an addition to antibacterial therapy.Antibacterial therapy remains the main recommendation for the treatment of bacterial eye infections, both in the anterior segment and in deeper lesions. In most countries, drugs from the group of fluoroquinolones and aminoglycosides are more often prescribed empirically, to which an acceptable level of sensitivity of microorganisms remains. Among aminoglycosides, the greatest sensitivity of eye infection pathogens is currently determined to netilmicin.The review examines the prospects and effectiveness of using netilmicin as monotherapy, as well as in combination with fluoroquinolones for topical treatment of bacterial infections in ophthalmology, and provides examples of the successful use of netilmicin.